SAFETY AND EFFICIENCY OF MEDICINAL VEGETABLE RAW MATERIALS OF THE TARAXACUM OFFICINALE, COLLECTED IN THE DISTRICTS EXPERIENCING THE ANTHROPOGENIC STRAIN - N. A. Dyakova; A. A. Mundra; A. Y. Slivkin (Разработка и регистрация лекарственных средств, 2019)
The interrelation between accumulation of serious metals and water-soluble polysaccharides in roots of a Taraxacum officinale, collected in the territory of the Voronezh region in the natural biogeocenoses which are influenced various anthropogenic influence is studied. Results of a research of the selected samples of roots of a dandelion medicinal show, in general, ecologically safe condition of the studied medicinal vegetable raw materials. On the content of arsenic only two samples which are brought together close combined heat and power plants of «VOGRES» and the chemical company LLC «Bormash» are recognized as unsatisfactory. On accumulation of water-soluble polysaccharides of roots of a Taraxacum officinale serious metals don't exert the expressed impact.